αE-catenin regulates actin dynamics independently of cadherin-mediated cell–cell adhesion - Benjamin, Jacqueline M. (The Rockefeller University Press, 2010)
αE-catenin binds the cell–cell adhesion complex of E-cadherin and β-catenin (β-cat) and regulates filamentous actin (F-actin) dynamics. In vitro, binding of αE-catenin to the E-cadherin–β-cat complex lowers αE-catenin affinity for F-actin, and αE-catenin alone can bind F-actin and inhibit Arp2/3 complex–mediated actin polymerization. In cells, to test whether αE-catenin regulates actin dynamics independently of the cadherin complex, the cytosolic αE-catenin pool was sequestered to mitochondria without affecting overall levels of αE-catenin or the cadherin–catenin complex. Sequestering cytosolic αE-catenin to mitochondria alters lamellipodia architecture and increases membrane dynamics and cell migration without affecting cell–cell adhesion. In contrast, sequestration of cytosolic αE-catenin to the plasma membrane reduces membrane dynamics. These results demonstrate that the cytosolic pool of αE-catenin regulates actin dynamics independently of cell–cell adhesion.